Medidas hemodinâmicas aórticas e rigidez arterial em pacientes com DPOC e associação com perfil clínico e funcional na exacerbação aguda e no período de recuperação - Agnoleto, Aline Galvão (Universidade Federal de São Carlos, 2018)
Background: Acute exacerbation of COPD negatively affects the disease, impairs lung function, functional capacity and health status and increases the risk for the development of cardiovascular diseases (CVD), and the recovery period is a period of great vulnerability for the patient. Arterial stiffness (AS) and central hemodynamic measures are recognized as predictors of cardiovascular morbidity and mortality in COPD. However, the knowledge about hemodynamic variables and AS, as well as their associations with the clinical and functional profile in acute exacerbation and in the recovery period in patients with COPD is still scarce. Objectives: To investigate the hemodynamic measurements, AS, clinical and functional profile in patients with COPD in acute exacerbation and 30 days after discharge and to determine the relationship between these variables. Methods: Forty-one patients with COPD were recruited and nine completed the evaluations in this study. Hemodynamic variables obtained by pulse wave analysis (PWA), central and peripheral systolic and diastolic blood pressures (cSBP, cDBP, pSBP and pDBP, respectively), central and peripheral pulse pressures (PPc and PPp), augmentated pressure (AP), pulse wave velocity (PWV), pulse transit time (PTT) and amplification index (AIx) were measured by the Sphygmocor device; the functional profile evaluated by the handgrip strength test (HS) using a dynamometer (Jamar®); dyspnea was measured by the modified Medical Research Council scale (mMRC); the state of health by the COPD Assessment Test (CAT) and pulmonary function by the spirometry test. Results: Analysis between the acute and recovery period demonstrated significant differences in aortic and peripheral measurements (cSBP, pSBP, cPP, pPP, AP), whereas AS (PWV and AIx) did not change significantly between the moments. Independent of the period (acute or recovery) we found a negative relationship between AS and functional capacity (PWV and HS: r=-0.82; r=-0.76, respectively) and positive between PTT and HS (r=0.75). We also observed significant relationship between AS and lung function (PWV and AIx vs FEV1%pred: r=-0.78 and r=0.68, respectively) at acute exacerbation. Conclusion: Aortic and peripheral hemodynamics were more impaired at AECOPD than at recovery period; and the AS, as a cardiovascular risk factor, is associated to functional capacity and lung function both at exacerbation and recovery. Key words: chronic obstructive pulmonary disease; acute exacerbation; aortic; arterial stiffness; pulse wave velocity; pulse wave analysis.
Aortic hemodynamics and arterial stiffness in COPD patients and its association with clinical and functional profile at acute and recovery period
Keywords: Doença pulmonar obstrutiva crônica; Exacerbação aguda; Aórtica; Rigidez arterial; Chronic obstructive pulmonary disease; Acute exacerbation; Aaortic; Arterial stiffness; Pulse wave velocity; Pulse wave analysis; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL